2022
DOI: 10.5530/pj.2022.14.106
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds from Purslane (Portulaca oleracea L.) and Star Anise (Illicium verum Hook) as SARS-CoV-2 Antiviral Agent via Dual Inhibitor Mechanism: In Silico Approach

Abstract: Sample preparationThe bioactive components found in purslane are apigenin, isorhamnetin, and luteolin. Meanwhile, star anise has shikimic acid, illicinole, and illicinone A. Data were provided by PubChem. Furthermore, non-structural target protein databases TMPRSS2 and PLpro were obtained from RSCB PDB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…21,16,30 Molecular complexes can be formed from weak bond interactions, hydrogen bond interactions have an important role in drug molecules, which play a role in maintaining molecular complexes so that they can trigger biological responses to protein targets. 16,31,32…”
Section: Resultsmentioning
confidence: 99%
“…21,16,30 Molecular complexes can be formed from weak bond interactions, hydrogen bond interactions have an important role in drug molecules, which play a role in maintaining molecular complexes so that they can trigger biological responses to protein targets. 16,31,32…”
Section: Resultsmentioning
confidence: 99%
“…42 There are also pi-cation, pi-alkyl, pi-stacked amide, vdw, and unfavorable donor-donor bonds that form a relatively negative binding affinity. [43][44][45][46][47][48][49][50]…”
Section: Resultsmentioning
confidence: 99%
“…Drug molecule analysis of compounds used five rules by Lipinski include mass molecule less than 500 Dalton, hydrogen bond donor less than 5, hydrogen bond acceptor less than 10, logP calculation (lipophilicity) less than 5, and molar reactivity about 40-130. 17,36 The result of Lipinski analysis showed that kaempferol and lignan compounds complied of five rules, however betulinic acid compound complied of three rules. Based on a statement of Kharisma et al that analysis for drug molecule of compounds prediction followed in minimal two from all Lipinski rules.…”
Section: Drug Molecule Analysis Of Compoundsmentioning
confidence: 99%